Case Report: Coexistence of Alzheimer-Type Neuropathology in Fragile X-Associated Tremor Ataxia Syndrome - Salcedo-Arellano, Maria Jimena; Sanchez, Desiree; Wang, Jun Yi; McLennan, Yingratana A.; Clark, Courtney Jessica; Juarez, Pablo; Schneider, Andrea; Tassone, Flora; Hagerman, Randi J.; Martínez-Cerdeño, Verónica (Frontiers in Neuroscience, 2021)
This case documents the co-occurrence of the fragile X-associated tremor ataxia syndrome (FXTAS) and Alzheimer-type neuropathology in a 71-year-old premutation carrier with 85 CGG repeats in the fragile X mental retardation 1 (FMR1) gene, in addition to an apolipoprotein E (APOE) ε4 allele. FXTAS and Alzheimer’s Disease (AD) are late-onset neurodegenerative diseases that share overlapping cognitive deficits including processing speed, working memory and executive function. The prevalence of coexistent FXTAS-AD pathology remains unknown. The clinical picture in this case was marked with rapid cognitive decline between age 67 and 71 years in addition to remarkable MRI changes. Over the 16 months between the two clinical evaluations, the brain atrophied 4.12% while the lateral ventricles increased 26.4% and white matter hyperintensities (WMH) volume increased 15.6%. Other regions atrophied substantially faster than the whole brain included the thalamus (-6.28%), globus pallidus (-10.95%), hippocampus (-6.95%), and amygdala (-7.58%). A detailed postmortem assessment included an MRI with confluent WMH and evidence of cerebral microbleeds (CMB). The histopathological study demonstrated FXTAS inclusions in neurons and astrocytes, a widespread presence of phosphorylated tau protein and, amyloid β plaques in cortical areas and the hippocampus. CMBs were noticed in the precentral gyrus, middle temporal gyrus, visual cortex, and brainstem. There were high amounts of iron deposits in the globus pallidus and the putamen consistent with MRI findings. We hypothesize that coexistent FXTAS-AD neuropathology contributed to the steep decline in cognitive abilities.